2010
DOI: 10.1098/rspb.2010.1968
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium relictuminfection and MHC diversity in the house sparrow (Passer domesticus)

Abstract: Antagonistic coevolution between hosts and parasites has been proposed as a mechanism maintaining genetic diversity in both host and parasite populations. In particular, the high level of genetic diversity usually observed at the major histocompatibility complex (MHC) is generally thought to be maintained by parasite-driven selection. Among the possible ways through which parasites can maintain MHC diversity, diversifying selection has received relatively less attention. This hypothesis is based on the idea th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 85 publications
(93 reference statements)
5
80
0
1
Order By: Relevance
“…Although population-specific associations between Mhc alleles and Plasmodium species have been reported in house sparrow populations [17,19], the functional differences between these alleles were not assessed, and our results imply that different alleles linked with disease may be similar at their ABS even in unrelated host species. The functional similarity across species suggests that Mhc-linked malaria resistance can be a valuable area for further research to understand the genetic basis of variation in infection in wild systems.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although population-specific associations between Mhc alleles and Plasmodium species have been reported in house sparrow populations [17,19], the functional differences between these alleles were not assessed, and our results imply that different alleles linked with disease may be similar at their ABS even in unrelated host species. The functional similarity across species suggests that Mhc-linked malaria resistance can be a valuable area for further research to understand the genetic basis of variation in infection in wild systems.…”
Section: Discussionmentioning
confidence: 98%
“…Of five studies investigating a link between passerine Mhc class I and Plasmodium infection, only two studies, both on house sparrows (Passer domesticus), presented sequence information for Mhc alleles identified as being linked to P. relictum infection (GenBank nos EU715815 -EU715817 and EF429132; [18,19]). The similarity of these house sparrow alleles to the Mhc supertypes examined in this study at their putative ABS (to infer functional similarity) was assessed by combining these additional four alleles with our 755 functional class I alleles and re-running the k-means clustering algorithm [41].…”
Section: (E) Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, these hosts may be resistant to the infection. This could be owing to adaptations of the immune system (such as those associated with major histocompatibility complex [62][63][64] or host cell surface proteins [65]), the lack of necessary machinery of the parasite to invade and persist in certain hosts, or both. Palinauskas et al [7] demonstrated that experimentally challenged host species differed in their level of resistance towards Plasmodium relictum.…”
Section: Quiscalus Quiscula C U L E X P I P I E N S C U L E X R E S Tmentioning
confidence: 99%
“…The second mechanism, rare-allele advantage, assumes that parasites are most likely to adapt to the most frequent host genotypes, and thus rare alleles are more often associated with parasite resistance (Bodmer 1972;Potts and Wakeland 1990;Borghans et al 2004). If the selective pressure from a parasite changes temporally (Hill et al 1991) or spatially (Kloch et al 2010;Loiseau et al 2011), this change may drive the third mechanism, fluctuating selection (Hedrick 2002).…”
Section: Introductionmentioning
confidence: 99%